2012
DOI: 10.1007/s00520-012-1392-0
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in poor-performance status small cell lung cancer patients: is there a mandatory role for chemotherapy?

Abstract: Median survival for ECOG PS 4 patients treated with chemotherapy in our series was extremely short with a high rate of early deaths. ECOG PS 3 patients also showed a poor survival. These data suggest that we need a more comprehensive approach and further studies, regarding the palliative care of this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
1
10
1
1
Order By: Relevance
“…Therefore, even in the case of patients with PS 4, it was considered there was clinical benefit from first-line chemotherapy. In addition, the effects seen in our study were slightly inferior to the results of a prospective clinical trial in patients under 70 years having PS 3, which showed a MST of 6.9 to 7.1 months 10) . There is a limitation to our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, even in the case of patients with PS 4, it was considered there was clinical benefit from first-line chemotherapy. In addition, the effects seen in our study were slightly inferior to the results of a prospective clinical trial in patients under 70 years having PS 3, which showed a MST of 6.9 to 7.1 months 10) . There is a limitation to our study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a reference point to select either chemotherapy or supportive care is not clear; furthermore, there have only been a few reports citing the use of chemotherapy for SCLC patients with extremely poor PS. Indeed, there have been only two retrospective reports mentioning PS 4 patients in this context 9,10) . Sakuragi et al reported on five PS 4 patients 9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum LDH düzeylerinin KHAK'de yüksek olarak saptandığı ve önemli prognostik faktörler arasında olduğu bilinir 18,19 . Çalışmamızda KHAK'li hastalarda hem adenokanser hem de skuamoz hücreli kansere göre anlamlı derecede yüksek LDH düzeyi elde ettik.…”
Section: Bulgularunclassified
“…Using metastatic soft tissue sarcoma (STS) as an example, systemic chemotherapy generally offers moderate response rates (10-40%) [74] with a significant potential for toxicity, even at reduced doses [75]. The most widely used prognostic indicator is performance status: patients with performance status 3-4 are unlikely to benefit from systemic treatments, whereas the decision can be less clear in those with a performance status of 2 [79][80][81]. There are therefore patients unlikely to gain 'palliative' benefit from starting chemotherapy who are also at risk of dying soon after treatment initiation.…”
Section: When and When Not To Treat With Oncological Therapymentioning
confidence: 99%